O empirismo e a filosofia crítica de Kant: ’Segunda posição do pensamento para a objetividade’ no ’Conceito preliminar’ enciclopédico da lógica especulativa (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: Hegel deals in the Zweite Stellung des Gedankens zur Objektivität with empiricism and transcendental philosophy. In accordance to his system of philosophy Hegel covers three important aspects in dealing with philosophical thoughts. First, Hegel criticizes previous philosophical positions. Empiricism and transcendental philosophy are rejected as inadequate and one-sided. Secondly Hegel asserts his own philosophical system offering a conclusive form of philosophy. Thirdly Hegel values transcendental positions as substantial contributions to the development of philosophy. Empiricism and transcendental philosophy are therefore not only rejected, but also recognized as imperfect but nonetheless true sub-projects of philosophy. Hegel not only criticizes his predecessors he also knows what his philosophy owes to them. He renewed his criticism of Kant. However, his criticism misses the project of Kant. KEYWORDS: Hegel, Logic, Concept.